Low folate levels may protect against colorectal cancer. Issue 10 (25th April 2006) - Van Guelpen, B; Hultdin, J; Johansson, I; Hallmans, G; Stenling, R; Riboli, E; Winkvist, A; Palmqvist, R
Abstract : Background and aims: Dietary folate is believed to protect against colorectal cancer (CRC). However, few studies have addressed the role of circulating levels of folate. The aim of this study was to relate prediagnostic plasma folate and homocysteine concentrations and the methylenetetrahydrofolate reductase (MTHFR) 677C>T and 1298A>C polymorphisms to the risk of developing CRC. Subjects: Subjects were 226 cases and 437 matched referents from the population based Northern Sweden Health and Disease Cohort. Results: We observed a bell-shaped association between plasma folate concentrations and CRC risk; multivariate odds ratio for middle versus lowest quintile 2.00 (95% confidence interval (CI) 1.13–3.56). In subjects with follow up times greater than the median of 4.2 years however, plasma folate concentrations were strongly positively related to CRC risk; multivariate odds ratio for highest versus lowest quintile 3.87 (95% CI 1.52–9.87; p trend = 0.007). Homocysteine was not associated with CRC risk. Multivariate odds ratios for the MTHFR polymorphisms were, for 677 TT versus CC, 0.41 (95% CI 0.19–0.85; p trend = 0.062), and for 1298 CC versus AA, 1.62 (95% CI 0.94–2.81; p trend = 0.028). Interaction analysis suggested that the result for 1298A>C may have been largely due to linkage disequilibrium with 677C>T. The reduced CRC risk in 677 TT homozygotes was independent of plasma folate status. Conclusions: Our findings suggest a decreased CRC risk in subjects with low folate status. This possibility of a detrimental component to the role of folate in carcinogenesis could have implications in the ongoing debate in Europe concerning mandatory folate fortification of foods.